Neuropathology in 1984: a deadly shot into the heart of Europe - Budka, Herbert (Free Neuropathology, 2024)
Just 40 years ago, Europe was divided into the Eastern communist bloc, which included the Czechoslovak Socialist Republic (ČSSR) and was dominated by the now historical Soviet Union, and the Western bloc comprising democracies such as Austria. The Iron Curtain, a heavily guarded and deadly border zone, separated the two blocs and constrained, in prison style, the populations of the Eastern bloc. The present neuropathological article relates the sad fate of František Faktor, a 33 years-old Czech who was shot by ČSSR border guards when attempting to flee to Austria at the border between Česke Velenice and Gmünd. František Faktor was found dead on November 5th, 1984, on Austrian soil some 500 meters from the border. ČSSR authorities claimed that he was shot when still within their territory, then ran some 900 meters to the other side of the border and died there. Neuropathology demonstrated a gunshot injury of the spinal canal, with transverse lesioning of the spinal cord predominating at Th10 that must have resulted in immediate paraplegia. This finding proved that ČSSR border guards had shot on Austrian territory, resulting in a major diplomatic éclat between both countries. After the implosion of the communist governments of the Eastern bloc in 1989, relations between Czechia and Austria started to normalise. By now, the Gmünd/Česke Velenice region has developed an exemplary good local neighbourhood and the former border has become virtually irrelevant. Attempts to bring justice have started in Czechia as well as other countries behind the past Iron Curtain and some former Czechoslovak officials held responsible for border killings were legally prosecuted. The present article demonstrates how a small medico-scientific discipline such as neuropathology can contribute to assess critical political events in our world.